Brief Report: Calculating the Ankylosing Spondylitis Disease Activity Score If the Conventional C‐Reactive Protein Level Is Below the Limit of Detection or If High‐Sensitivity C‐Reactive Protein Is Used: An Analysis in the DESIR Cohort. Issue 2 (February 2015) - Machado, Pedro; Navarro‐Compán, Victoria; Landewé, Robert; van Gaalen, Floris A.; Roux, Christian; van der Heijde, Désirée
<x xml:space="preserve">Abstract</x> Objective The Ankylosing Spondylitis Disease Activity Score (ASDAS) is a composite measure of disease activity in axial spondyloarthritis. The aims of this study were to determine the most appropriate method for calculating the ASDAS using the C‐reactive protein (CRP) level when the conventional CRP level was below the limit of detection, to determine how low CRP values obtained by high‐sensitivity CRP (hsCRP) measurement influence ASDAS‐CRP results, and to test agreement between different ASDAS formulae. Methods Patients with axial spondyloarthritis who had a conventional CRP level below the limit of detection (5 mg/liter) were selected (n = 257). The ASDAS–conventional CRP with 11 different imputations for the conventional CRP value (range 0–5 mg/liter, at 0.5‐mg/liter intervals) was calculated. The ASDAS‐hsCRP and ASDAS using the erythrocyte sedimentation rate (ESR) were also calculated. Agreement between the ASDAS formulae was tested. Results The ASDAS‐hsCRP showed better agreement with the ASDAS‐CRP calculated using the conventional CRP imputation values of 1.5 and 2.0 mg/liter and with the ASDAS‐ESR than with other imputed formulae. Disagreement occurred mainly in lower disease activity states (inactive/moderate disease activity). When the CRP value was <2 mg/liter, the resulting ASDAS‐CRP scores may have been inappropriately low. Conclusion When the conventional CRP level is below the limit of detection or when the hsCRP level is <2 mg/liter, the constant value of 2 mg/liter should be used to calculate the ASDAS‐CRP score. There is good agreement between the ASDAS‐hsCRP and ASDAS‐ESR; however, formulae are not interchangeable.